NATURAL MOISTURIZER BASED FORMULATION OF GREEN GRASS JELLY (CYCLEA BARBATA MIERS) WITH ALOE VERA ADDITION - Harianti, Santi Fitri; Harismah, Kun (Jurnal Dedikasi, 2020)
Moisturizer is one of cosmetics used for dry skin care and can make skin become moist and soft. Natural material can be used to maintain water content in the skin and soften skin is Aloe vera. Aloe vera contains minerals, vitamins A, C, E and B12. In addition to Aloe vera to maintain antioxidants in the skin is green grass jelly because it has flavonoid content. Content contained in Aloe vera and green grass jelly can be used for making natural moisturizers because at this time many moisturizers that contain harmful chemicals. This observation was to analyze differences in concentration of Aloe vera and green grass jelly on moisturizers and analyze antioxidant activity of green grass jelly. Method used in making this moisturizer is mixing with green grass jelly formulation (2.5%; 5%; 7.5%) + Aloe vera (2.5%, 5%, 7.5%, 10%), and non-sample formulation treatment. Analysis of this experimental data was qualitative on moisturizers and quantitatively to calculate levels of flavonoids in green grass jelly. Results of this study indicate that difference in concentration of Aloe vera + green grass jelly greatly affects parameters of good moisturizer used, and greater addition of green grass jelly concentration greater flavonoid content in moisturizer.